2001
DOI: 10.1039/b108940b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection and evaluation of rna aptamers that recognize arginine-rich-motif model peptide on a quartz-crystal microbalance

Abstract: To study RNA-peptide interactions, we performed an in vitro selection of RNA on a simple alpha-helical peptide-immobilized quartz-crystal microbalance (QCM) and evaluated the association constants (10(7) M-1) of the selected RNA to the model peptide on the same QCM plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…We quantify the distribution of associated secondary-structural motifs using tree graphs and graph theory measures of size and complexity (particularly, tree diameter and second smallest Laplacian eigenvalue, which are defined in the Materials and Methods section). Our results show that such random RNA pools heavily favor (>90%) simple topological structures like linear stem-loop and low-branching motifs, as confirmed by many known aptamers (Bae et al 2002;Fukusho et al 2002;Khoo et al 2002;Komatsu et al 2002;Ulrich et al 2002;Zinnen et al 2002;Meli et al 2003;Laserson et al 2004). For example, the 25-nt and 40-nt pools are almost completely populated by hairpin and stem-bulge-stem-loop structures.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We quantify the distribution of associated secondary-structural motifs using tree graphs and graph theory measures of size and complexity (particularly, tree diameter and second smallest Laplacian eigenvalue, which are defined in the Materials and Methods section). Our results show that such random RNA pools heavily favor (>90%) simple topological structures like linear stem-loop and low-branching motifs, as confirmed by many known aptamers (Bae et al 2002;Fukusho et al 2002;Khoo et al 2002;Komatsu et al 2002;Ulrich et al 2002;Zinnen et al 2002;Meli et al 2003;Laserson et al 2004). For example, the 25-nt and 40-nt pools are almost completely populated by hairpin and stem-bulge-stem-loop structures.…”
Section: Introductionmentioning
confidence: 61%
“…Indeed, in vitro selection experiments have revealed novel functional RNAs from random sequence pools, including a wide range of RNA aptamers that bind to particular compounds, such as ATP, antibiotics or proteins, and catalytic RNAs (Wilson and Szostak 1999;Hodgson and Suga 2004); see the collection of several hundred aptamers in the Aptamer Database (http:// aptamer.icmb.utexas.edu). However, an analysis of existing aptamers has shown that RNA sequences isolated from selection experiments tend to have simple topologies (Bae et al 2002;Fukusho et al 2002;Khoo et al 2002;Komatsu et al 2002;Ulrich et al 2002;Zinnen et al 2002;Meli et al 2003;Laserson et al 2004). That is, linear or slightly branched structures occur far more often than highly compact structures.…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] To prevent any nonspecific interactions on the electrode surface during measurement, PEG molecules known to inhibit nonspecific interactions were used as a spacer to immobilize the KIX peptide. [41] The degree of immobilization at each step was confirmed directly from frequency decreases (mass increases) by using the QCM in water.…”
Section: Preparation Of the Kid Peptidementioning
confidence: 99%
“…Matsuno et al (2001a) designed and synthesized specific helical peptides on the basis of a well-conserved sequence of natural DNA-binding proteins and used these to investigate the sequence specificity and recognition rules of the DNA-binding proteins. A novel variation on the DNA biosensor was presented by Fukusho et al (2002) who used a peptide immobilized QCM to study RNA-peptide interactions. They conclude that five arginines were not enough to bind specifically to particular internal loops, but played an important role in recognizing specific RNAs.…”
Section: Dna-protein Interactionsmentioning
confidence: 99%